Analyse de la composante sémantique lexicale de l’inversion locative en anglais - Gérard MÉLIS (E-REA)
This article examines the noncanonical structure known as the locative inversion, which can be described as : < Constituent1 C1 (fronted locative expression) + verb V + Constituent2 C2 (postposed subject) >. There are two general types of constraints regulating this structure : on the one hand, the construction is said to be constrained by the verb which must be unaccusative, and, on the other hand, the locative inversion seems to be regulated by some principles of information packaging (in this respect, the fronted location is thematic while the postposed subject is focalized) and by the fact that the verb involved must be semantically light. This article discusses these two analyses (the syntactic analysis of unaccusativity, the discursive analysis developed in terms of information structure). Unaccusativity is problematic as a consistent category, and the postposed subject is not always focalized new information while the fronted location is not systematically given information. My aim is to show that the semantic relationship between the fronted location C1 and the verb is a significant parameter as far as the acceptability of the locative inversion is concerned. In this respect, there are two cases : a/ the location is an argument of the verb, b/ there is a tight relationship between the verb and the locative constituent.